FKASA alumni committee launched - UMP, PNC
Universiti Malaysia Pahang's (UMP) Faculty of Civil Engineering & Earth Resources (FKASA) held a hi-tea gathering at The Legend Hotel in Kuala Lumpur on April 2, 2011, to commemorate the official launch of the faculty’s alumni membership drive committee.